2022
DOI: 10.2147/jir.s380818
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Value of Dysregulated miR-10a-3p in Patients with Severe Pneumonia

Abstract: Previous studies have shown that microRNA is involved in regulating a variety of human inflammatory diseases. The purpose of this study was to investigate the expression of miR-10a-3p in the blood of patients with severe pneumonia and evaluate its value in the diagnosis and prognosis of severe pneumonia. Patients and Methods: Seventy patients with severe pneumonia and 75 healthy individuals were included in this study. Venous blood of all subjects was obtained for RT-qPCR analysis to obtain the relative expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…For example, miR‐10a‐3p is abnormally expressed in patients with severe pneumonia and could be used for its early detection and risk assessment. [ 37 ] It has also been reported that miR‐10a‐3p regulates immunological balance and relieves renal injury in lupus nephritis via the JAK2/STAT3 pathway. [ 38 ] To date, the biological function of miR‐10a‐3p in CNI ED has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR‐10a‐3p is abnormally expressed in patients with severe pneumonia and could be used for its early detection and risk assessment. [ 37 ] It has also been reported that miR‐10a‐3p regulates immunological balance and relieves renal injury in lupus nephritis via the JAK2/STAT3 pathway. [ 38 ] To date, the biological function of miR‐10a‐3p in CNI ED has not yet been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on the prognosis of SCAP, either the study population was outside the ICU[8-10], the risk factors for mortality were not readily available clinically [9,10], no relevant predictive model was developed [11], or the model developed was not externally validated [10,12]. Generally, only a few comprehensive and accurate evaluation systems can adequately assess the prognosis of patients with SCAP admitted to the ICU at this stage.…”
Section: Introductionmentioning
confidence: 99%